Comorbid major depression in obsessive-compulsive disorder patients - Quarantini, Lucas C.; Torres, Albina Rodrigues [UNESP]; Sampaio, Aline S.; Fossaluza, Victor; Mathis, Maria Alice De; Do Rosário, Maria Conceição; Fontenelle, Leonardo F.; Ferrão, Ygor A.; Cordioli, Aristides Volpato; Petribu, Katia; Hounie, Ana G.; Miguel, Eurípedes C.; et al. (Elsevier, 2011)
Although major depressive disorder (MDD) has been consistently considered the most frequent complication of obsessive-compulsive disorder (OCD), little is known about the clinical characteristics of patients with both disorders. This study assessed 815 Brazilian OCD patients using a comprehensive psychiatric evaluation. Clinical and demographic variables, including OCD symptom dimensions, were compared among OCD patients with and without MDD. Our findings showed that prevalence rates of current MDD (32%) and lifetime MDD (67.5%) were similar for both sexes in this study. In addition, patients with comorbid MDD had higher severity scores of OCD symptoms. There was no preferential association of MDD with any particular OCD symptom dimension. This study supports the notion that depressed OCD patients present more severe general psychopathology. © 2011 Elsevier Inc. All rights reserved.
Keywords: adult; aggression; anxiety; Brazil; cleaning; comorbidity; disease severity; female; human; lifespan; major clinical study; major depression; male; obsessive compulsive disorder; prevalence; religion; Adult; Comorbidity; Depressive Disorder, Major; Female; Humans; Male; Middle Aged; Obsessive-Compulsive Disorder; Prevalence; Severity of Illness Index